Insidensi Virus dan Cendawan pada Biji dan Umbi Bawang Merah - Ana Septiana Saputri; Efi Toding Tondok; Sri Hendrastuti Hidayat (Jurnal Fitopatologi Indonesia, 2018)
Incidence of Viruses and Fungi on True Shallot Seed and Shallot Bulb Shallot is an important vegetable in Indonesia. Shallot farmers generally use bulbs as planting material even though there is an option to use true shallot seed (TSS). One important criteria for a good seed quality as planting material is pathogen free. Research was conducted to detect and identify viruses and fungi from TSS and shallot seed bulbs cultivars Bima, Bauji, Thailand, and Tuk-Tuk. Virus detection was carried out by DIBA (dot immunobinding assay) method using specific antiserum to OYDV, SLV, SYSV, and GCLV. Detection and identification of fungi was carried out by blotter test method and polymerase chain reaction. Infection of OYDV, GCLV, SYSV, and SLV were only detected in shallot bulbs with infection rates ranging from 66% to 100%. Four species of fungi were detected in TSS and bulbs, i.e. Aspergillus niger, A.flavus, F. solani, and Rhizopus sp; whereas F.oxysporum was only found in bulbs. All isolates of F. oxysporum was pathogenic and cause disease incidence up to 55%. Pathogenic isolate of F. oxysporum had 100% homology to those isolate from China and USA on the spesies level and 91.2% to those isolate from India and USA to the forma spesies level.